Sulfate anion templation of a neutral pseudorotaxane assembly using an indolocarbazole threading component. - Chmielewski, M; Zhao, L; Brown, A; Curiel, D; Sambrook, MR; Thompson, A; Santos, S; Felix, V; Davis, J; Beer, P (2008)
The first example of anion templated pseudorotaxane formation between two neutral components in solution and in surface assembled monolayers is described.